COVID-19 in caribbean islands - Mora-Alvarado, Darner A. (2023)
The present study describes real time evolution of COVID-19 in thirteen Caribbean islands more than two years after the start of the global health crisis, caused by the new coronavirus SARS-CoV-2, originally detected in Wuhan, China, on December 17, 2019. The descriptive evolution of confirmed cases and deaths is presented in two stages: the first as of October 30, 2021, and the second as of April 8, 2022. The estimated population of these countries islands is 29,605,675 inhabitants distributed heterogeneously, on islands with more than 10 million inhabitants in Cuba with 11,400,000 inhabitants, Haiti and the Dominican Republic with 11,400,000 inhabitants and 10,850,000 respectively, located in Hispaniola Island. The other island nations have fewer than 3 million inhabitants; among them: Jamaica, Trinidad and Tobago, Grenada, Saint Lucia, Bahamas, Barbados, Dominica, Saint Vincent and the Grenadines, Saint Kitts and Nevis. In the three nations, there have been 2,206,567 confirmed infections with 22,472 deaths for an average lethality of 1.02%. The countries with the most infections and deaths are Cuba and the Dominican Republic. Advances in vaccination indicate that, as of April 8, 2022, Cuba leads both in Caribbean Islands, as well as worldwide and in America the continent.